Model Policies to Protect U.S. Fire-Based EMS Responders From Workplace Stress and Violence. (August 2022) - Taylor, Jennifer A.; Murray, Regan M.; Davis, Andrea L.; Brandt-Rauf, Sherry; Allen, Joseph A.; Borse, Robert; Pellechia, Diane; Picone, David
The stress and violence to fire-based emergency medical service responders (SAVER) Systems-Level Checklist is an organizational-level intervention to address stress and violence in emergency medical service (EMS), focused on the development of policy and training. Fire and EMS leadership, first responders, dispatchers, and labor union representatives participated in the SAVER Model Policy Collaborative to develop model policies that resulted from the most feasible checklist items. ThinkLets technology was employed to achieve consensus on the model policies, and an Action SWOT analysis was then conducted to assess facilitators and barriers to policy implementation. The resultant model policies are a systems-level workplace violence intervention for the U.S. fire and rescue service that is ready for implementation. Expected improvements to organizational outcomes such as burnout, job engagement, and job satisfaction are anticipated, as are decreasing assaults and injuries. The SAVER Model Policies have the potential to inform national standards and regulations on workplace violence in EMS.